2021
DOI: 10.1016/j.tig.2020.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Histone Ubiquitination: An Integrative Signaling Platform in Genome Stability

Abstract: Complex mechanisms are in place to maintain genome stability. Ubiquitination of chromatin plays a central role in these mechanisms. The ever-growing complexity of the ubiquitin (Ub) code and of chromatin modifications and dynamics challenges our ability to fully understand how histone ubiquitination regulates genome stability. Here we review the current knowledge on specific, low-abundant histone ubiquitination events that are highly regulated within the cellular DNA damage response (DDR), with particular emph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(95 citation statements)
references
References 123 publications
(159 reference statements)
0
95
0
Order By: Relevance
“…One of the first chromatin events at DSBs is the phosphorylation of the histone variant H2A.X [ 7 ] (ÎłH2A.X in mammals, ÎłH2A in yeast, and ÎłH2A.v in Drosophila), which can spread up to two Megabases around the break site [ 8 ] and initiates a multitude of downstream repair events (reviewed in [ 9 ]). In addition to ÎłH2A.X, many other chromatin changes occur at the break site, such as the ubiquitination or acetylation of histones, which often serve as binding platforms for repair proteins (reviewed in [ 10 , 11 ]). Besides DSB-induced histone modifications, cell cycle-driven chromatin changes also influence repair by directly controlling repair pathway usage.…”
Section: Introductionmentioning
confidence: 99%
“…One of the first chromatin events at DSBs is the phosphorylation of the histone variant H2A.X [ 7 ] (ÎłH2A.X in mammals, ÎłH2A in yeast, and ÎłH2A.v in Drosophila), which can spread up to two Megabases around the break site [ 8 ] and initiates a multitude of downstream repair events (reviewed in [ 9 ]). In addition to ÎłH2A.X, many other chromatin changes occur at the break site, such as the ubiquitination or acetylation of histones, which often serve as binding platforms for repair proteins (reviewed in [ 10 , 11 ]). Besides DSB-induced histone modifications, cell cycle-driven chromatin changes also influence repair by directly controlling repair pathway usage.…”
Section: Introductionmentioning
confidence: 99%
“…The left domain of the enzyme determines the specific recognition of the target protein, and the right domain locates the E2 enzyme to transfer ubiquitin molecules. As a result of protein ubiquitination, the labeled protein is broken down by proteases into smaller peptides, amino acids and ubiquitin that can be reused ( 26 – 28 ). In terms of the previously identified interactions between several MAGE proteins and RING domain proteins, it was found that they will form complexes, such as MAGE-A2/C2-triple motif (TRIM)28, MAGE-B18-ligand of numb-protein X and MAGE-G1-non-structural maintenance of chromosomes element 1 (NSE1) complexes ( 29 ).…”
Section: Relationship Between the Mage Family And Ubiquitination And Diseasementioning
confidence: 99%
“…Studies over the past two decades have established that histone ubiquitination establishes a platform for the recruitment of a variety of DNA damage response proteins including BRCA1 to DSB (Mattiroli & Penengo, 2021;Uckelmann & Sixma, 2017). Histone ubiquitination is initiated by E3 ubiquitin ligase RNF8, which is recruited to DSB by ÎłH2AX-MDC1 signaling.…”
Section: Recruitment Of Brca1 To Dsbmentioning
confidence: 99%
“…The recruitment of 53BP1 to DSB requires histone ubiquitination, which is est ablished by ÎłH2AX-MDC1-RNF8-RNF168 signaling pathway (Mattiroli & Penengo, 2021;Uckelmann & Sixma, 2017). Interestingly, although H2ax KO, Rnf8 KO, or Rnf168 KO abolishes the recruitment of 53BP1 to DSB, none of them rescues the embryonic lethality of Brca1 Δ11/Δ11 mice (Zong et al, 2019).…”
Section: Rescue Of Hr Repair Defects Caused By Brca1 Deficiencymentioning
confidence: 99%